Two Pentatricopeptide Repeat Proteins Are Required for the Splicing of nad5 Introns in Maize - Yang, Huanhuan; Xiu, Zhihui; Wang, Le; Cao, Shi-Kai; Li, Xiulan; Sun, Feng; Tan, Bao-Cai (Frontiers in Plant Science, 2020)
Mitochondrial genes in flowering plants contain predominantly group II introns that require precise splicing before translation into functional proteins. Splicing of these introns is facilitated by various nucleus-encoded splicing factors. Due to lethality of mutants, functions of many splicing factors have not been revealed. Here, we report the function of two P-type PPR proteins PPR101 and PPR231, and their role in maize seed development. PPR101 and PPR231 are targeted to mitochondria. Null mutation of PPR101 and PPR231 arrests embryo and endosperm development, generating empty pericarp and small kernel phenotype respectively in maize. Loss-of-function in PPR101 abolishes the splicing of nad5 intron 2, and reduces the splicing of nad5 intron 1. Loss-of-function in PPR231 reduces the splicing of nad5 introns 1, 2, 3 and nad2 intron 3. The absence of Nad5 protein eliminates assembly of complex I, and activates the expression of alternative oxidase AOX2. These results indicate that both PPR101 and PPR231 are required for mitochondrial nad5 introns 1 and 2 splicing, while PPR231 is also required for nad5 intron 3 and nad2 intron 3. Both genes are essential to complex I assembly, mitochondrial function, and maize seed development. This work reveals that the splicing of a single intron involves multiple PPRs.